2014
DOI: 10.1159/000363515
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Induced by Lipid Peroxidation Is Related with Inflammation of Demyelination and Neurodegeneration in Multiple Sclerosis

Abstract: Background: Multiple sclerosis (MS) is a chronic autoimmune demyelination disorder of the central nervous system (CNS) and its etiology remains unknown. The inflammatory environment in demyelinating lesions leads to the generation of oxygen- and nitrogen-free radicals as well as proinflammatory cytokines, which contribute to the development and progression of multiple sclerosis. Inflammation can lead to oxidative stress and vice versa. Thus, oxidative stress is involved in the inflammation leading demyelinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(55 citation statements)
references
References 25 publications
1
53
1
Order By: Relevance
“…For instance, after W6 of CPZ administration we observed a strong reduction of MPs in the corpus callosum. Although most of the remaining MPs still express PDK1 and there is a trend toward decreased PDH activity compared with CTRL, we did not detect a significantly increased production of HP [1][2][3][4][5][6][7][8][9][10][11][12][13] C]lactate at that time point, which may be explained by the limited sensitivity of HP 13 C MRSI to lower MP number. Furthermore, the lack of increase in the HP [1-13 C]lactate-topyruvate ratios in two of seven mice at W4 (Fig.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…For instance, after W6 of CPZ administration we observed a strong reduction of MPs in the corpus callosum. Although most of the remaining MPs still express PDK1 and there is a trend toward decreased PDH activity compared with CTRL, we did not detect a significantly increased production of HP [1][2][3][4][5][6][7][8][9][10][11][12][13] C]lactate at that time point, which may be explained by the limited sensitivity of HP 13 C MRSI to lower MP number. Furthermore, the lack of increase in the HP [1-13 C]lactate-topyruvate ratios in two of seven mice at W4 (Fig.…”
Section: Discussioncontrasting
confidence: 60%
“…In the vast majority of cases, demyelinating lesions present a high inflammatory component, with elevated density of activated microglia/macrophages (mononuclear phagocytes, MPs) (4-6). Importantly, evidence suggests that proinflammatory MPs are one of the most abundant sources of reactive oxygen species (7), which mediate demyelination and axonal injury (8). Due to their central role in MS pathogenesis, noninvasive imaging of proinflammatory MPs would be of high importance for monitoring progression and response to antiinflammatory therapeutic approaches.…”
mentioning
confidence: 99%
“…Deposition or loss of the myelin sheath results in irreversible axonal degeneration and affects neuronal connectivity [73]. Defective myelination, due to either genetic or acquired factors, can lead to neurological diseases including multiple sclerosis [74], leukodystrophies [75], and peripheral neuropathies [76]. Exposure to high dose of X-ray radiation reduced the numbers of migratory neuroblasts, and significantly less brain myelination was observed as well [77].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al examined levels of MDA and TAC in peripheral blood and in the CSF of RRMS patients 7 days before methylprednisolone (MP) treatment and 1 month after MP treatment. They found that the increase in OS markers precedes inflammatory response in MS patients and MP treatment reduces the neuroinflammatory attack by decreasing brain antioxidant enzymes (111). Ozone autohemotherapy is an emerging therapeutic technique that can change brain metabolism.…”
Section: Corticosteroids In Relapses-the Importance Of Os and Antioximentioning
confidence: 99%